PENERIMAAN PARTAI POLITIK ISLAM DI PTAIN: - Cucu Nurhayati; Hamka Hasan (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2015)
UIN Syarif Hidayatullah Jakarta is an institution representing Islam as values, religion, ideology, rituals, and symbols. With these characters, Islamic political parties gain a high sympathy in this institution. Having approximately 25,000 students, 1000 academic and administrative staffs, UIN should have been a mass basis for Islamic political parties. Despite the assumption that Islamic community is a potential vote raiser for Islamic political parties, the parties were not significantly considered by the UIN Jakarta academicians. This study focuses on the students’ acceptance on political parties by their party affiliations. 450 respondents were questioned on this matter and 51,1% of them stated that they are not affiliated or a part of Islamic political parties (while the 48,9% stated that they are). Only 42% of respondents (140 students) are affiliated to Islamic parties, while 58% are not.